Caracterização de resíduo da indústria de beneficiamento de milho - Zanotto, Caroline (2011)
This study aimed to perform the characterization of the waste generated by the corn processing industry, known as corn steep liquor, to assess the concentrations of substrates in order to found a viable form of treatment or reuse. The corn steep liquor contains large amounts of nitrogen, amino acids and other nutrients, is primarily used as a food supplement in the manufacture of feed and nutrient source in fermentation processes. Were carried out physic-chemical and microbiological as COD, BOD, acidity, total sugar, molds and chromatographic analysis and found that the organic matter concentration was high, requiring treatment before being released, the sample pH was acid after the first of corn steep liquor, indicating the presence of microorganisms in the fermentation process, the pH value of 3,7 was found biochemical oxygen demand was 1812 mg.dm-3, the chemical oxygen demand was 3670 mg.dm-3, and analysis on high performance liquid chromatography showed the presence of carboxylic acids, probably of small chains, compared with the intensity of the peaks. By analyzing the results showed that the corn steep liquor has potencial for reuse in industrial processes as a treatment.